The Effect Of Current And Future Land Use On House Prices - Guillaume Pouyanne; Monique Dantas; Frédéric Gaschet (European Regional Science Association (ERSA), 2013)
The control of urban sprawl often involves policies of allowable use zoning. By protecting large areas from development, such policies may, in fact, provoke ?leapfrog? development through their inflationary effect on the land and property markets in the area which is already urbanised. This inflationary effect results in particular from the positive external effects generated on neighbouring property by the land classified as unbuildable. This effect is dealt with in the vast amount of literature on the open space premium, where the capitalised premium in property prices arises from the positive externalities generated by open space as well as from the absence of negative external effects generated by land conversion. In this literature, the premium is derived uniquely from current land use. The future use of the land is nevertheless an important component of the premium. However, it is rarely taken into account, and then only in terms of whether the open space is permanent or temporary. This article proposes an evaluation of the impact of current and future surrounding land use on property prices. In a one-kilometre radius around the site of the transaction, we combine the actual use of land (residential, agricultural, forest...) with its membership of a zoning category (which determines the future destination of land: buildable or unbuildable; if buildable, high or low density...). We use a spatial hedonic model, corrected from endogeneity of the regressors thanks to the Fingleton-Le Gallo?s procedure (2008). We show that both the current use and the future use of surrounding land have an impact on the price of a transaction. First, it is important to take into account the classification of land as buildable: thus urban green space is certainly responsible for a positive premium, but only on condition that it is not classified as buildable. Second, the fact that land is classified as unbuildable can have an ambiguous effect: forests protected as sensitive natural open spaces do bring a positive premium whereas forests protected for sylviculture tend to provoke depreciation in property prices due to the nuisances associated with their exploitation. Third, the ?type of buildability? may have an influence on prices: the dispersed nature of future development appears to cause fewer nuisances than big, uniform future development.
Keywords: R14; R52; 330; land use; open space; capitalisation